2014
DOI: 10.1371/journal.pone.0089981
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Reviews of Animal Studies; Missing Link in Translational Research?

Abstract: BackgroundThe methodological quality of animal studies is an important factor hampering the translation of results from animal studies to a clinical setting. Systematic reviews of animal studies may provide a suitable method to assess and thereby improve their methodological quality.ObjectivesThe aims of this study were: 1) to evaluate the risk of bias assessment in animal-based systematic reviews, and 2) to study the internal validity of the primary animal studies included in these systematic reviews.Data Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 16 publications
3
61
0
Order By: Relevance
“…This trend might reflect increasing awareness by both researchers and authorities of the importance of reporting, and it is consistent with recent evidence from a random sample of life sciences publications [28]. However, despite the many systematic reviews revealing flaws in experimental design and conduct since Ioannidis’ seminal opinion paper [38], and the wealth of solutions that have since been proposed [2,5,32,39], little progress has been made. Like Baker et al in 2014 [33], we did not find convincing evidence that reporting had increased from applications authorized before (2008) to those authorized after (2012) publication of the ARRIVE guidelines.…”
Section: Discussionsupporting
confidence: 69%
“…This trend might reflect increasing awareness by both researchers and authorities of the importance of reporting, and it is consistent with recent evidence from a random sample of life sciences publications [28]. However, despite the many systematic reviews revealing flaws in experimental design and conduct since Ioannidis’ seminal opinion paper [38], and the wealth of solutions that have since been proposed [2,5,32,39], little progress has been made. Like Baker et al in 2014 [33], we did not find convincing evidence that reporting had increased from applications authorized before (2008) to those authorized after (2012) publication of the ARRIVE guidelines.…”
Section: Discussionsupporting
confidence: 69%
“…One evaluation of such research found that main quality features such as proper randomization and blinding of investigators assessing outcomes are rarely adhered to . Other efforts have addressed biases in animal studies of experimental treatments or toxicology assessments of chemicals . Instead of performing more such animal studies and retrospective meta‐analyses thereof that highlight more of these same biases, research in these fields should be recast with better study methods, and a prospective design of meta‐analyses that includes all the studies launched.…”
Section: Meta‐analyses Of Experimental Animal Studiesmentioning
confidence: 99%
“…This translation is affected by numerous factors, such as biological differences between species, internal validity, differences in experimental design between animal studies and clinical trials, insufficient reporting, and publication bias. 39,40 Therefore, the rationalized use of animal and sample size discrepancy can be reviewed whereas disparity in translation of animal experiment to clinical trial can be resolved by pooling the inconsistencies in the results and poor sample size of different studies through meta-analysis based on specific questions. If it is considered that the effect and biases are potentially the same, then validation of the signal cannot be proven.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 However, the results from these experiments must be accurate. 41,42 Reproducible and consistent results from animal models can provide reliable data of relevance to human medicine.…”
Section: Systematic Review and Meta-analysis Of Literaturementioning
confidence: 99%